Use of Eggshell-Alginate Composite as Adsorbent for Rhodamine B - Sholihah, Mar'Atus
Rhodamine B is the most commonly used dyes for textile industry as a red dye. Rhodamine B have a potency as a carcinogenic compound, and it is dangerous if it's pollute the environment. In this research, removal of Rhodamine B compound with adsorption method was examined using eggshell-alginate composite as an adsorbent. Eggshell-alginate composite (EAC) successfully synthesized and characterized with FTIR, SEM, TGA, and Surface Area Analyzer with BET and BJH method analysis. EAC adsorb Rhodamine B optimally with composition eggshell powder : alginate in 2 : I. As for optimum condition for adsorbing Rhodamine B using EAC is with contact time 3 hour, pH 4, adsorbent dose 0,05 gram/25 mL of Rhodamine B solution, and initial concentration of Rhodamine B 400 ppm. Maximum adsorption capacity to adsorb Rhodamine B with EAC is 151,51 mg/g and have adsorption habits taking pseudo-second order kinetic model and Langmuir adsorption isothenn. Study of thennodynamics adsorptions show that adsorption of Rhodamine B with EAC has 1-f value 6212,22 J /mol, and S0 value I ,79 J /moi.K.